A novel polymeric micelle used for in vivo MR imaging tracking of neural stem cells in acute ischemic stroke. Issue 25 (7th March 2017) - Lu, Liejing; Wang, Yong; Cao, Minghui; Chen, Meiwei; Lin, Bingling; Duan, Xiaohui; Zhang, Fang; Mao, Jiaji; Shuai, Xintao; Shen, Jun
Abstract : Novel cationic polymeric micelles based on biodegradable poly(aspartic acid-dimethylethanediamine)–lysine–cholic acid were synthesized for in vivo tracking therapeutic stem cells using MRI. Abstract : Transplantation of neural stem cells (NSCs) is a promising treatment strategy for acute ischemic stroke. In vivo tracking of the therapeutic stem cells in the host brain after transplantation is essential not only to ensure the safety and efficacy of the treatment, but also to better understand their migrational dynamics and regeneration potential. Many polymeric nanoparticles have been developed to label stem cells for in vivo tracking by magnetic resonance imaging (MRI), optical imaging (OI) or other imaging modalities. However, the non-degradability and presence of cellular toxicity of the nanoparticles restrict their clinical applications. In this study, we developed a novel cationic polymeric micelles based on amphipathic polymer of biodegradable hydrophilic poly(aspartic acid-dimethylethanediamine) (PAsp(DMA)) that were conjugated with two molecules of hydrophobic cholic acid (CA) by lysine. Image labels, superparamagnetic iron oxide nanoparticles (SPIONs) and fluorescent nile red were simultaneously loaded into the micelles to label NSCs. The labeling capacity, efficiency and cytotoxicity of the cationic micelles were determined. The in vivo MRI tracking of the therapeutic NSCs in acute ischemic stroke was also explored. Our results showed that this type of cationic polymeric micelles achieved a high efficient and safe labeling of NSCs and resulted in reliable in vivo MRI tracking of therapeutic stem cells in acute ischemic stroke, but without detrimental effect. The cationic, biodegradable polymeric micelles are highly translatable for clinical application and can be used as a versatile nanoplatform for stem cell labeling and subsequently in vivo tracking in regenerative medicine.